REKONSTRUKSI PERTANGGUNGJAWABAN PIDANA DALAM KASUS PENGANIAYAAN BERAT YANG MENYEBABKAN KEMATIAN ANALISIS YURIDIS TERHADAP PROBLEMATIC QUALIFICATION DAN IMPLEMENTASI KUHP BARU - Akhmad Faishal; Siti Humulhaer; Bachtiar Kemal Harahap; M Zaenudin Ibrahim; Mochamad Fachri Muzhaffar (Berajah Journal, 2026)
This study analyzes the problems of legal qualification and criminal liability in cases of aggravated assault resulting in death under Article 354 paragraph (2) of the Indonesian Criminal Code, examined from the perspectives of substantive and procedural criminal law. The analysis focuses on the complexity of proving the element of intent (dolus), particularly the distinction between intent causing serious bodily injury and intent resulting in death, as well as the implications of the enactment of Law Number 1 of 2023 concerning the New Criminal Code for the criminal sentencing system. The research employs a normative legal method using statutory, conceptual, and case approaches. The findings reveal the existence of a grey area between aggravated assault resulting in death and homicide under Article 338 of the Criminal Code, which frequently leads to disparities in judicial decisions. The new Criminal Code provides clearer systematic provisions regarding the qualification of criminal offenses; however, challenges remain in proving the causal link between the act of assault and the resulting death. This study recommends the development of alternative causality theories in the context of aggravated assault cases, particularly through the application of a foreseeability test, as well as the incorporation of restorative justice mechanisms as an alternative resolution in cases involving serious assault with asymmetric power relations.